2020
DOI: 10.1038/s41598-020-57499-5
|View full text |Cite
|
Sign up to set email alerts
|

Rice pyramided line IRBB67 (Xa4/Xa7) homeostasis under combined stress of high temperature and bacterial blight

Abstract: Rice bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae (Xoo) implies substantial yield loss to rice. In times of climate change, increasing temperatures are observed and further acceleration is expected worldwide. Increasing temperature often turns into inhibition of host plant defense to pathogens. Recently, a reduced resistance in rice IRBB4 carrying Xa4, but an increase in resistance in IRBB7 carrying Xa7 resistance by increasing temperature has been reported. Influence of high temperature on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 77 publications
1
34
0
Order By: Relevance
“…Thirdly, genotype plays an important role in the way plants integrate multistress signals. For example, high temperatures decrease the resistance to X. oryzae of rice carrying Xa4 resistance but increase resistance of rice carrying Xa7 resistance , and this is correlated with genotype-specific transcriptomic profiles under the multistress combination ( Table 1 ; Dossa et al , 2020 ). The importance of genotype is supported by the involvement of PBS3 , an actor in SA signaling, in the age-dependent trade-off between two abiotic stresses and immune responses in Arabidopsis ( Berens et al , 2019 ): immune responses are reduced by drought and high salinity in older leaves, but not in younger leaves in which PBS3 antagonizes the trade-off.…”
Section: Multistress Signals Orchestrate Plant Transcriptomic Responsmentioning
confidence: 99%
“…Thirdly, genotype plays an important role in the way plants integrate multistress signals. For example, high temperatures decrease the resistance to X. oryzae of rice carrying Xa4 resistance but increase resistance of rice carrying Xa7 resistance , and this is correlated with genotype-specific transcriptomic profiles under the multistress combination ( Table 1 ; Dossa et al , 2020 ). The importance of genotype is supported by the involvement of PBS3 , an actor in SA signaling, in the age-dependent trade-off between two abiotic stresses and immune responses in Arabidopsis ( Berens et al , 2019 ): immune responses are reduced by drought and high salinity in older leaves, but not in younger leaves in which PBS3 antagonizes the trade-off.…”
Section: Multistress Signals Orchestrate Plant Transcriptomic Responsmentioning
confidence: 99%
“…These contrasting scenarios raise concerns about durability of single R gene and different gene combinations in the scenario of a rapidly changing climate. Recently, Dossa et al (2020) demonstrated that near isogenic line IRBB 67 (owning BB resistance genes Xa4 and Xa7) did not show any difference in lesion length at both lower and higher temperature regimes, indicating that the reduced effectiveness of Xa4 at higher temperature did not affect the resistance level of IRBB 67.…”
Section: Impact Of Climate On Bb Resistance Genesmentioning
confidence: 99%
“…Insects propagate more at higher temperature and show increased feeding voracity across an increasing temperature range (Havko et al, 2020). In rice, high temperature contributes to bacterial blight development in field situations, and the disease severity is particularly high in the hot season (Dossa et al, 2020). For more examples related to high temperature-induced disease susceptibility we refer to a recent review (Cohen & Leach, 2020).…”
Section: Biochemical Processes Under High Temperaturementioning
confidence: 99%
“…Bacterial blight caused by Xanthomonas oryzae pv. oryzae(Xoo ) leads to substantial yield loss in rice (Dossa et al, 2020). Xa7, one of the Resistance genes (R -genes) against pathogens (Zhang et al, 2015), effectively confers resistance to Xoo at high temperatures, but not at low temperature (Cohen et al, 2017;Dossa et al, 2020;Webb et al, 2010).…”
Section: Biochemical Processes Under High Temperaturementioning
confidence: 99%
See 1 more Smart Citation